2018
DOI: 10.1111/apt.14801
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐viral therapy is associated with improved survival but is underutilised in patients with hepatitis B virus‐related hepatocellular carcinoma: real‐world east and west experience

Abstract: Anti-viral therapy improved overall survival in patients with HBV-related HCC across cancer stages and treatment types but was underutilised at both US and Asia centres. Expanded use of anti-viral therapy in HBV-related HCC and better linkage-to-care for HBV patients are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 38 publications
1
39
0
1
Order By: Relevance
“…It is not clear why survival in MAFLD‐related HCC is unaffected by cirrhosis status, which is different than what has been reported in chronic hepatitis B‐related HCC, ( 19,37 ) although consistent with the limited earlier literature in MAFLD‐related HCC. ( 17,20‐22 ) One potential explanation is that the superior liver function in patients without cirrhosis was offset by the later presentation due to a decrease in screening; however, cirrhosis status was not associated with mortality after adjustment for meeting Milan criteria (Table 4).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It is not clear why survival in MAFLD‐related HCC is unaffected by cirrhosis status, which is different than what has been reported in chronic hepatitis B‐related HCC, ( 19,37 ) although consistent with the limited earlier literature in MAFLD‐related HCC. ( 17,20‐22 ) One potential explanation is that the superior liver function in patients without cirrhosis was offset by the later presentation due to a decrease in screening; however, cirrhosis status was not associated with mortality after adjustment for meeting Milan criteria (Table 4).…”
Section: Discussionmentioning
confidence: 56%
“…(16,17) In the case of chronic hepatitis B-related HCC, cirrhosis is associated with poorer prognosis. (18,19) The effect of cirrhosis on MAFLD-related HCC has been investigated only in small cohorts and primarily in Caucasian populations. (17,(20)(21)(22) Unlike chronic hepatitis B, current practice guidelines do not recommend routine HCC surveillance for noncirrhotic MAFLD because the incidence of HCC in this population is too low to justify surveillance.…”
mentioning
confidence: 99%
“…Many reports have shown that treatments based on etiology are beneficial to improve HCC patients' prognosis. [30][31][32][33][34] In order to identify the prognostic value of the constructed model, we tested an internal cohort, and the results were consistent with those of the primary cohort. Furthermore, even when we divided the whole cohort into a 2:1 ratio, as for training and validation, the results were indistinguishable (data not shown).…”
Section: Discussionmentioning
confidence: 88%
“…Several professional societal guidelines recommend HCC surveillance in at‐risk populations, including those with cirrhosis, using ultrasound (US) with or without alpha‐foetoprotein (AFP) . However, HCC surveillance in patients with cirrhosis does not have level I evidence and has been primarily supported by cohort studies demonstrating an association with earlier stage detection, greater likelihood of receiving curative therapy and improved survival . These studies have notable limitations including potential for lead‐time bias, length time bias and residual confounding .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] However, HCC surveillance in patients with cirrhosis does not have level I evidence and has been primarily supported by cohort studies demonstrating an association with earlier stage detection, greater likelihood of receiving curative therapy and improved survival. [9][10][11] These studies have notable limitations including potential for leadtime bias, length time bias and residual confounding. 12 It is well recognized that US and AFP can have limited sensitivity for early stage HCC detection in clinical practice, with a recent meta-analysis reporting a sensitivity of only 63% for early-stage HCC detection when using the two tests in combination.…”
mentioning
confidence: 99%